Elevated Viral Restriction Factor Levels in Cortical Blood Vessels in Schizophrenia - Siegel, Benjamin I.; Sengupta, Elizabeth J.; Edelson, Jessica R.; Lewis, David A.; Volk, David W. (Biological psychiatry (1969), 2014)
Higher tissue transcript levels of immune-related markers—including the recently discovered viral restriction factor interferon-induced transmembrane protein (IFITM), which inhibits viral entry and replication—have been reported in the prefrontal cortex in schizophrenia. Interestingly, mouse models of neuroinflammation have higher IFITM levels and deficits in γ-aminobutyric acid (GABA)-related markers that are similar to findings in schizophrenia, suggesting that a shared pathogenetic process might underlie diverse cortical pathology in the disorder. However, the cell types that overexpress IFITM messenger RNA (mRNA) in schizophrenia are unknown, and it is unclear whether higher IFITM mRNA levels are associated with lower GABA-related marker levels in the same schizophrenia subjects. We used quantitative polymerase chain reaction and in situ hybridization with film and grain counting analyses to quantify IFITM mRNA levels in prefrontal cortex area 9 of 57 schizophrenia and 57 healthy comparison subjects and in antipsychotic-exposed monkeys. Quantitative polymerase chain reaction and in situ hybridization film analysis revealed markedly elevated IFITM mRNA levels (+114% and +117%, respectively) in prefrontal gray matter in schizophrenia. Interestingly, emulsion-dipped, Nissl-stained sections from schizophrenia and comparison subjects revealed IFITM mRNA expression in pia mater and blood vessels. The IFITM grain density over blood vessels was 71% higher in schizophrenia. The IFITM mRNA levels were negatively correlated with GABA-related mRNAs in the same schizophrenia subjects. The finding that schizophrenia subjects with higher IFITM mRNA levels in cortical blood vessels have greater disturbances in cortical GABA neurons suggests that these cell-type distinct pathological disturbances might be influenced by a shared upstream insult that involves immune activation.